Individualist–Collectivist Culture and Trust Radius: A Multilevel Approach. (February 2015) - van Hoorn, André
We apply a multilevel approach to examine empirically the nexus between individualist and collectivist culture on the one hand and people's radius of trust on the other. People's trust level (i.e., the intensity with which people trust other people) has been extensively studied. Increasingly, however, researchers are seeing a need to move beyond trust level and study trust radius (i.e., the width of the circle of people among whom a certain trust level exists) as the second quintessential component of trust. Results for up to 44, 845 individuals from 36 countries show, first, that we can validly apply multilevel modeling to the study of trust radius. Second, consistent with prior theoretical expectations, individualism is associated with a broader trust radius, whereas collectivism is associated with a narrower trust radius. Considering the strength of the associations found, trust radius might be best understood as an inherent part of the individualism–collectivism cultural syndrome. The key contribution of this note is to reveal how exactly individualism–collectivism relates to trust, specifically its radius. In addition, the note demonstrates the feasibility of a multilevel approach to studying trust radius with much potential for follow-up research on this most vital trust construct.